CROATIA: THE 28th MEMBER STATE OF THE EUROPEAN UNION - DAN VĂTĂMAN (Challenges of the Knowledge Society)
In an enlarged European Union of 27 Member States, convinced that the successive enlargements have been a success both for the European Union and the Member States which acceded to it, thus contributing to stability, development and prosperity throughout Europe, the leaders of Member States considered that this process must continue, ensuring the success of future enlargement of the Union, for a better response to the many challenges they face. Croatia completed its negotiations on the European Union membership in June 2011 and the European Council has designated 1 July 2013 as the date of Croatia's accession to the European Union, provided that all the procedures required for full membership are completed by that date. Therefore, this study aims to analyze the progress made by Croatia in its preparations for accession to the European Union and if this country continues to meet the Copenhagen criteria and has the ability to take on the obligations of membership.